Higher energy availability may support hemoglobin mass adaptation during a 21-day period at normobaric hypoxia and normoxia in female skiers - Kettunen, O.; Kuorelahti, T.; Linnamo, V.; Ihalainen, J. K.; Mikkonen, R. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Low energy availability (EA) may be detrimental to an athletes` health and performance [1], but the interaction between EA and altitude training adaptations warrants exploration. Therefore, the present study investigated EA during a 21-day period of normobaric "live high, train low" (LHTL) and examined whether athletes with positive hemoglobin mass (Hbmass) responses had different EA compared to the athletes with neutral / negative responses.